Dilematika perbedaan kurikulum ditengah gelombang otonomi daerah pada bidang pendidikan - Trisiana, Anita - (Widya Wacana: Jurnal Ilmiah, 2012)
Abstraksi : Policy implementation  encompasses those action by public and private individuals ( or group ) that are directed at the achievement of objective set fort in prior policy decisions.  This includes both one time efforts to transform decisions into operasional term, as well as continuing efforts to achieve the large and small change  mandated by policy decisions. The result of the implementation governmental policy in Indonesian have been executed by all school, The problem faced by each School in Indonesian is still lower the understanding to curriculum 2004,and stiil limited fund and also medium and equipment supporting curriculum execution 2004.  The strategy that done by a school to face the problem of About Curriculum Execution 2004 was by improving educator professionalism ( learn ) through seminar activity, workshop, training have local and national scale and other and also prepare the medium and equipment supporter by self-fund Keyword : Perubahan Kurikulum, Otonomi  Daerah, Kebijakan Pemerintah